ICMI : antara status quo dan demokratisasi - Wahid, Abdurrahman; Ali-Fauzi, Nasrullah, 1967- (Bandung : Mizan, 1995)
Opinions and articles on ICMI, the Indonesian Association of Muslim Intellectuals; previously published in magazines
Includes bibliographical references and index
Keywords: ICMI (Organization); Intellectuals -- Indonesia -- Societies, etc; Islam -- Indonesia -- Societies, etc